Constructing the Core Competencies of Smart Teaching for Chinese Pre-service Art Teachers in Higher Education (International Journal of Environmental Sciences, 2025)
Amid the rapid advancement of smart education, the development of smart teaching core competencies has emerged as a focal point in educational research and practice. Drawing upon competency theory and adopting the Iceberg Model to structure capabilities, this study systematically reviews smart teaching competency frameworks proposed by international organizations and major nations. Anchored in the context of China’s art education, it explores the theoretical connotation and structural composition of smart teaching core competencies for preservice art teachers. The study suggests that these competencies should encompass not only general abilities such as technology application, instructional organization, and evaluative feedback, but also discipline-specific attributes—such as digital media–based aesthetic facilitation and immersive instructional design. Based on this perspective, a preliminary three-layered competency structure is proposed, integrating explicit knowledge and skills, implicit awareness and dispositions, and cross-dimensional integrated capabilities. This framework provides theoretical support for the subsequent construction of competency indicator systems and empirical analysis, while also offering guidance for the digital transformation of art education and the enhancement of teachers’ digital literacy.